Pkd1 Regulates Lymphatic Vascular Morphogenesis during Development - Baptiste Coxam; Amélie Sabine; Neil I. Bower; Kelly A. Smith; Cathy Pichol-Thievend; Renae Skoczylas; Jonathan W. Astin; Emmanuelle Frampton; Muriel Jaquet; Philip S. Crosier; Robert G. Parton; Natasha L. Harvey; et al. (Cell Reports, 2014)
Lymphatic vessels arise during development through sprouting of precursor cells from veins, which is regulated by known signaling and transcriptional mechanisms. The ongoing elaboration of vessels to form a network is less well understood. This involves cell polarization, coordinated migration, adhesion, mixing, regression, and shape rearrangements. We identified a zebrafish mutant, lymphatic and cardiac defects 1 (lyc1), with reduced lymphatic vessel development. A mutation in polycystic kidney disease 1a was responsible for the phenotype. PKD1 is the most frequently mutated gene in autosomal dominant polycystic kidney disease (ADPKD). Initial lymphatic precursor sprouting is normal in lyc1 mutants, but ongoing migration fails. Loss of Pkd1 in mice has no effect on precursor sprouting but leads to failed morphogenesis of the subcutaneous lymphatic network. Individual lymphatic endothelial cells display defective polarity, elongation, and adherens junctions. This work identifies a highly selective and unexpected role for Pkd1 in lymphatic vessel morphogenesis during development.